Glucagon like peptide-1 (GLP-1) agonists and cardiometabolic protection: historical development and future challenges - Francisco Westermeier; Enrique Z. Fisman (Cardiovascular Diabetology)
Abstract Glucagon-like peptide-1 receptor agonists (GLP-1RAs) have revolutionized the treatment of cardiometabolic diseases, extending their therapeutic applications far beyond glycemic control in type 2 diabetes (T2D) and obesity. This editorial synthesizes key milestones, from the discovery of GLP-1 to recent clinical trials highlighting the pleiotropic effects of GLP-1RAs in addressing the interconnected spectrum of cardiometabolic conditions, with a focus on cardiovascular, renal, and hepatic benefits. In addition, as GLP-1RAs continue to reshape the management of cardiometabolic disease and global public health, we discuss future challenges to better elucidate their mechanisms of cardiometabolic protection and maximize their therapeutic potential. Graphical abstract